PENDIDIKAN BAHASA INDONESIA DAN PENGUATAN NASIONALISME - Lanny Koroh; Simon Sabon Ola (Jurnal Lazuardi, 2020)
Indonesian language as the identity of the Indonesian people can actually build the character of nationalism. Early Indonesian nationalism was sparked by colonialism as a common enemy. The originator of Indonesian nationalism today is a shared identity. The Indonesian language is one of those shared identities, alongside the flag, the state emblem and the national anthem. To strengthen the role of Indonesian in strengthening nationalism, it is necessary to have an output-oriented Indonesian language education that has a nationalist character, patriotism, and a sense of responsibility for the life of the Indonesian language. Indonesian language education must be able to reduce the pragmatism of the view on the importance of the Indonesian language, minimize the deviation from regulation on the Indonesian language, and foster the principle of learning Indonesian to achieve the Indonesian language in a global context.